2009
DOI: 10.1016/s1875-4597(09)60016-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Epidural and Intravenous Patient-controlled Analgesia on Bowel Activity After Cesarean Section: A Retrospective Study of 726 Chinese Patients

Abstract: PCA is safe and effective in alleviating postoperative pain following cesarean section. EPCA offers a faster return of bowel activity, lower VAS scores, and better patient satisfaction than IVPCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…There was statistically significant effect of spinal anesthesia versus general anesthesia in term of shorter mean time interval to normal intestinal sound (9.36 versus 22.29 hours), passage of flatus (12.66 versus 26.05 hours), first motion (15.57 versus 29.63 hours), and discharge from hospital (34.41 versus 56.18 hours), Also there was statistically significant effect of spinal anesthesia versus general anesthesia in term of less use of opioids (10.36% versus 13.47%), less use of nonsteroidal anti-inflammatory drugs (NSAID) (34.72% versus 80.31%), less incidence of distension (15.54% versus 40.41%), less incidence of ileus (0% versus 2.07%).This agrees with the result of Liu et al (7) which was done at China Medical University Hospital Taichung, Taiwan, which included 726 patients who consented to receive either regional or general anesthesia for elective cesarean section delivery. The study revealed that patients who underwent spinal or epidural anesthesia had a significantly quicker return of bowel activity than those who received general anesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…There was statistically significant effect of spinal anesthesia versus general anesthesia in term of shorter mean time interval to normal intestinal sound (9.36 versus 22.29 hours), passage of flatus (12.66 versus 26.05 hours), first motion (15.57 versus 29.63 hours), and discharge from hospital (34.41 versus 56.18 hours), Also there was statistically significant effect of spinal anesthesia versus general anesthesia in term of less use of opioids (10.36% versus 13.47%), less use of nonsteroidal anti-inflammatory drugs (NSAID) (34.72% versus 80.31%), less incidence of distension (15.54% versus 40.41%), less incidence of ileus (0% versus 2.07%).This agrees with the result of Liu et al (7) which was done at China Medical University Hospital Taichung, Taiwan, which included 726 patients who consented to receive either regional or general anesthesia for elective cesarean section delivery. The study revealed that patients who underwent spinal or epidural anesthesia had a significantly quicker return of bowel activity than those who received general anesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in previous studies, the time to first bowel sounds in gum-chewing groups ranged from 6.0 to 20.9 hr (Abd-El-Maeboud et al, 2009; Harma et al, 2009; Kafali et al, 2010; Mohsenzadeh Ledari et al, 2013; Satij & Cohen, 2006; Shang et al, 2010), and the time to first flatus ranged from 17.9 to 34.6 hr (Abd-El-Maeboud et al, 2009; Harma et al, 2009; Kafali et al, 2010; Mohsenzadeh Ledari et al, 2013; Satij & Cohen, 2006; Shang et al, 2010). The generally faster recovery of first bowel sounds and flatus in our study may be partly explained by all of our participants having received regional anesthesia, which results in a shorter time to the first passage of flatus than general anesthesia (Kafali et al, 2010; Liu et al, 2009). Another possible explanation for these differences is the use of different types of postsurgical analgesia.…”
Section: Discussionmentioning
confidence: 68%
“…Gastrointestinal motility may also be affected by small doses of opioids used in epidural anesthesia and to supplement spinal anesthesia if needed. Opioids suppress gastrointestinal function, reduce gastric motility and emptying, increase intestinal spasm, and decrease peristalsis (Liu et al, 2009;Miedema & Johnson, 2003). Despite evidence that postoperative ileus can be reduced (Chantarasorn & Tannirandorn, 2006;Charoenkwan, Phillipson, & Vutyavanich, 2007) and hospital stays can be shortened (Mangesi & Hofmeyr, 2007;Patolia, Hilliard, Toy, & Baker, 2001) by early oral feeding after uncomplicated cesarean delivery, oral feeding is traditionally withheld in Taiwan and other Asian countries until after resolution of post-cesarean ileus (Hsu, Hung, Chang, & Chang, 2013), often defined by passage of flatus and/or a bowel movement.…”
mentioning
confidence: 99%
“…Because of the blocking of this inhibitory reflex when patients use local analgesia with PCEA [14], the combination of an epidural opioid plus bupivacaine may help the recovery of gastrointestinal motility and reduce postoperative ileus [15,16]. A large retrospective study of 726 Chinese patients after cesarean section showed that the time to first flatus passage in women with epidural PCA was 1.33 days, while the time in women who used intravenous PCA was 1.51 days, which means a quicker recovery of gastrointestinal motility with PCEA [17]. However, that study did not include operations with gastrointestinal excision or anastomosis, and these factors may affect gastrointestinal motility more seriously.…”
Section: Discussionmentioning
confidence: 99%